Look at the researches in History of Mathematics Education from the analysis of the EBRAPEM (2014 and 2015) (Research, Society and Development, 2017)
Here we present part of a Research Project titled, Teaching Mathematics in Rio Grande do Norte (1920 to 1980), this study has as general objective to make an investigation of the annals referring to the XVIII and XIX Brazilian Meeting of Post- Graduation in Mathematics Education - EBRAPEM. This research gave us a perspective of how the researches in History of Mathematics Education (HEM) in Brazil are, since it is in this event that we have a sample of the works in progress or in the final phase of completion of the Graduate Programs Of the whole country. To do so, we used documentary research using the abstracts of the two annals of EBRAPEM, which were treated as documentary sources and analyzed within the context of the objectives of this research. (GIL, 1987). The articles analyzed were also classified according to seven thematic axes, as did Brito and Gomes (2009) in similar work. In this investigation we made a list of the themes, authors, institutions, sources and origin of productions. Thus, this enabled us to cast our gaze on these works and we perceive the thematic tendencies that are being researched in the different regions of Brazil, as well as the delimitations that exist by region and fields of scientific research and we identify the Graduate courses that develop researches In HEM. In this way we hope to contribute with the studies that go back to the History of Mathematical Education in our country, especially with the studies of the research group that we are currently part of, the Potiguar Group of Studies and Research